Matching service failures and recovery options toward satisfaction - Cantor, Victor John M. (Animo Repository, 2019)
Service failures are inevitable in any service delivery process that establishes the need for a good service recovery. This study aims to investigate the relationships among service recovery variables to develop appropriate recovery options considering different levels of failure severity and satisfaction. Using a scenario-based survey approach and structural equation modeling, the results are failure severity negatively relates to satisfaction; recovery justices positively relates to satisfaction regardless of the level of failure severity; complaining behavior strengthens (weakens) the relationship between the failure severity (recovery justices) and satisfaction; and relationship quality is a stronger predictor of post-purchase behavioral intentions than satisfaction. A service recovery matrix is proposed to depict appropriate recovery options for different situations. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.